2009
DOI: 10.4039/n08-063
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of Urophora quadrifasciata on spotted knapweed in the Arkansas Ozarks

Abstract: Periodic sweep-net sampling and capitula sampling were conducted between April and October 2007 to determine the seasonal phenology of Urophora quadrifasciata (Meigen) (Diptera: Tephritidae) on spotted knapweed, Centaurea stoebe subsp. micranthos (Gugler) Hayek (Asteraceae), in the Arkansas Ozarks of the United States of America. Urophora quadrifasciata produces up to three generations in Arkansas, rather than being bivoltine as in the northern United States of America. The first, second, and third generations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recently, the houndstongue root weevil Mogulones cruciger Herbst, which was released in Canada in 1997, has dispersed south across the US border where it may feed on native Boraginaceae (Andreas et al 2008). Similarly, the seed head fly Urophora quadrifasciata (Meigen) was introduced into Canada in the early 1970s but spread across the USA border and can now be found in much of North America, including the states of Arizona and Arkansas (Story 1985;Duguma et al 2009). In contrast, the eriophyid mite Eriophyes chondrillae (Canestrini) and the rust fungus Puccinia chondrillina Bubak and Sydow were released for control of Chondrilla juncea L. in the western USA but spread north to British Colombia, Canada (Julien and Griffiths 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the houndstongue root weevil Mogulones cruciger Herbst, which was released in Canada in 1997, has dispersed south across the US border where it may feed on native Boraginaceae (Andreas et al 2008). Similarly, the seed head fly Urophora quadrifasciata (Meigen) was introduced into Canada in the early 1970s but spread across the USA border and can now be found in much of North America, including the states of Arizona and Arkansas (Story 1985;Duguma et al 2009). In contrast, the eriophyid mite Eriophyes chondrillae (Canestrini) and the rust fungus Puccinia chondrillina Bubak and Sydow were released for control of Chondrilla juncea L. in the western USA but spread north to British Colombia, Canada (Julien and Griffiths 1998).…”
Section: Discussionmentioning
confidence: 97%
“…An example is the picture‐winged flies ( Urophora spp., Tephritidae) released against knapweeds. When attacking a target species, these species show a single generation in colder regions, but can have up to four generations in warm temperate zones (Duguma et al ., ). As growing seasons expand, at least some portion of the biological control agents will be able to exploit this increase by increasing the number of generations produced per growing season.…”
Section: Current Researchmentioning
confidence: 97%
“…This seedhead galling fly was introduced from Russia into Canada in 1980 and has since been redistributed or spread on its own to several states in the northeastern and northwestern United States (Story 2002). Duguma (2008) found that U. quadrifasciata reduced the number of seeds produced by spotted knapweed by 44% late in the season (Aug), at a time when plants are more environmentally stressed. However, the fly did not significantly reduce the number of seeds produced earlier in the season, a time when knapweed is most robust (Duguma 2008).…”
mentioning
confidence: 99%